Single-Stage Total Arch Replacement Including Resection of Kommerell Diverticulum in a Patient With Loeys-Dietz Syndrome. (September 2016) - Ong, Chin Siang; Kasai, Yuhei; Fukushima, Souta; Hibino, Narutoshi; Magruder, Trent; Suarez-Pierre, Alejandro; Cameron, Duke; Vricella, Luca
Loeys-Dietz syndrome (LDS) is an autosomal dominant genetic connective tissue disorder associated with aortic aneurysmal disease. Kommerell diverticulum (KD) is a rare aortic diverticulum, for which the indication for surgery and the surgical techniques remain subjects of debate. We describe our experience with a successful total aortic arch replacement including KD resection through a median sternotomy for a pediatric patient with LDS.